Combination therapy of gemcitabine or oral S-1 with the anti-VEGF monoclonal antibody bevacizumab for pancreatic neuroendocrine carcinoma - KASUYA, KAZUHIKO (D.A. Spandidos, 2012)
We previously reported that the administration of bevacizumab for pancreatic neuroendocrine tumors inhibited angiogenesis in the host, resulting in tumor growth inhibition. In light of these results, we compared the effect of bevacizumab/gemcitabine/S-1 combination therapy vs. bevacizumab monotherapy. The QGP-1 pancreatic neuroendocrine carcinoma cell line and the BxPC-3 ductal cell carcinoma cell line were transplanted into the subcutaneous tissue of mice, and the mice were treated for 3 weeks with bevacizumab [50 mg/kg intraperitoneally (i.p.) twice weekly], gemcitabine (240 mg/kg i.p. once weekly) and S-1 (10 mg/kg orally five times weekly). The antitumor effect and side effects were evaluated by measuring the tumor volume and weight and by changes in body weight, respectively. The tumor volume became smaller (from the maximum volume) in the group treated with bevacizumab, gemcitabine and S-1 (BGS) and the group treated with bevacizumab and gemcitabine (BG). A significant difference was noted in the tumor weight between the BG group and the group treated with bevacizumab alone. A relatively significant decrease in the body weight was observed in the BGS and BG groups. We conclude that gemcitabine is appropriate as a drug used in combination with bevacizumab for pancreatic neuroendocrine tumors.